Konsep manajemen pendidikan Islam - Hidayat, Sahrul Haj (Maliki Interdisciplinary Journal, 2024)
Everyone must prioritize their education. Education has always been a beacon of hope for the progress of society and individuals. The goal of education is basically to prepare students for life after school by imparting information and ideas. So that Islamic educational institutions can be planned, directed and supervised for a successful future and operate sustainably, professional management is needed. Because an institution without management will most likely experience problems and difficulty achieving its goals without management. The approach used in this research is the research approach used in this research is a theoretical approach. Researchers can assess and study the journal’s contribution to current theoretical knowledge by using a theoretical framework. The conclusion reached in this research is that the way of organizing or running Islamic educational institutions that utilize Islamic human resources and mobilize them to achieve the goals of Islamic education effectively and efficiently is known as Islamic education management. In general, the Al-Qur’an, Sunnah and Indonesian laws and regulations are the three (three) foundations for managing Islamic education. Islamic Education Management seeks to achieve goals through effective and efficient management of Islamic education resources. The implementation of Islamic education is based on a number of principles, including accountability, trust, honesty, justice and sincerity.